2021
DOI: 10.1111/den.14202
|View full text |Cite
|
Sign up to set email alerts
|

Beyond complete endoscopic healing: Goblet appearance using an endocytoscope to predict future sustained clinical remission in ulcerative colitis

Abstract: Objectives Complete endoscopic healing, defined as Mayo endoscopic score (MES) = 0, is an optimal target in the treatment of ulcerative colitis (UC). However, some patients with MES = 0 show clinical relapse within 12 months. Histologic goblet mucin depletion has emerged as a predictor of clinical relapse in patients with MES = 0. We observed goblet depletion in vivo using an endocytoscope, and analyzed the association between goblet appearance and future prognosis in UC patients. Methods In this retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In another study of UC subjects in ER (MES 0), EC reliably differentiates those in HR from those with histologically active disease (28). Similarly, Takishima et al (29) observed that number of Goblet cells quantified with EC predicted long-term sustained clinical remission in UC patients in ER (MES 0). Moreover, a recent study by Vitali et al (30) showed endocytoscopic assessment of microscopic disease activity in UC was more accurate than WL endoscopy and highly correlated with histological scores; furthermore, EC was shown as reliable as histology for prediction of clinical outcomes in UC patients.…”
Section: Endocytoscopymentioning
confidence: 86%
“…In another study of UC subjects in ER (MES 0), EC reliably differentiates those in HR from those with histologically active disease (28). Similarly, Takishima et al (29) observed that number of Goblet cells quantified with EC predicted long-term sustained clinical remission in UC patients in ER (MES 0). Moreover, a recent study by Vitali et al (30) showed endocytoscopic assessment of microscopic disease activity in UC was more accurate than WL endoscopy and highly correlated with histological scores; furthermore, EC was shown as reliable as histology for prediction of clinical outcomes in UC patients.…”
Section: Endocytoscopymentioning
confidence: 86%
“…A preliminary study confirmed that endocytoscopic evaluation of UC activity, graded with a dedicated score (ECS), had a stronger correlation with histology compared to normal endoscopic scores such as MES or UCEIS [70]. Another pivotal study showed how endocytoscopy could predict disease outcome by assessing the depletion of goblet cells [71]. Goblet cells are known to decrease in the presence of inflammation, but thus far, their assessment was only possible with conventional microscopy or CLE.…”
Section: Endocytoscopymentioning
confidence: 93%
“…Goblet cells are known to decrease in the presence of inflammation, but thus far, their assessment was only possible with conventional microscopy or CLE. In particular, the authors used the number of Goblet cells seen at endocytoscopy to stratify the risk of relapse in a large population of UC patients in endoscopic remission (MES 0) [71].…”
Section: Endocytoscopymentioning
confidence: 99%
“…Ueda et al classified EC appearance into four categories, EC-A, EC-B, EC-C, and EC-D, and showed correlations with MES, clinical activity, and pathological microscopic features of UC [ 197 ]. Kazumi et al evaluated goblet cells in 120 patients with an MES of 0 using endocytoscopy, and found that depleted goblet cells had a higher clinical relapse rate than non-depleted goblet cells ( p = 0.02) [ 198 ]. Maeda et al evaluated 52 patients with UC by endocytoscopy NBI, and the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of EC-NBI in diagnosing acute inflammation were 84.0%, 100%, 87.1%, 100% and 92.3%, respectively.…”
Section: Endocytoscopymentioning
confidence: 99%